A COMPARATIVE ANALYSIS OF PERCEIVED EASE OF USAGE DECISION OF E-BANKING IN Y AND Z GENERATION - Siti Alhamra Salqaura (SEAN Institute, 2023)
Consumer perceived ease of use is one of the important factors influencing the Y and Z generation usage decision of Mobile Banking. This study aims to compare the constructs of perceived ease of use in Y and Z generations in the context of digital banking. Sampling was done by purposive sampling method. Respondents are consumers among Y and Z generations with a total of 44 respondents. Data was collected using a questionnaire. Data analysis was performed using the Mann-Whitney U test through SPSS software version 20. The results showed no significant difference between the Y and Z generations in terms of usage decision of E-Banking based on perceived ease of use.